PENGARUH KINERJA KEUANGAN TERHADAP JUMLAH PENYALURAN KREDIT PADA PT. BPR SETIA KARIB ABADI SEMARANG - Pamor Nugroho; Saryadi Saryadi; Rodhiyah Rodhiyah (Universitas Diponegoro, 2013)
The soundness of the bank is used as a benchmark for bank management to assess whether the management of the bank had was done in line with the sound banking principles and in accordance with applicable regulations. PT.BPR Setia Karib Abadi Semarang is one company that is engaged in banking carries on business as Rural Bank. In the normal course of business of PT. BPR Setia Karib Abadi Semarang experience performing loans which fluctuate each year thereby affecting the company's financial performance and earnings. The purpose of this study to determine the influence of financial performance with CAMEL method to total loans at PT. BPR Setia Karib Abadi Semarang.This type of research is explanatory research. In this study took a sample of 4-year quarterly financial statements of the year 2009 - 2012. Technique analysis data using simple linear regression and multiple regression, with significance testing using the t test and F test with SPSS tools 17.Based on the results of analysis of CAR variable does not affect the amount of lending and give a contribution of 11.3%. KAP variables did not affect the amount of lending and contributed 0.02%. PPAP variables affect the amount of lending and influence contributed by 52.5%. ROA variable does not affect the amount of lending and give a contribution of 7.2%. ROA variable does not affect the amount of lending and give a contribution of 21.2%. LDR variables affect the amount of lending and influence contributed 70.7%. NPL variable does not affect the amount of lending and give a contribution of 0.03%. Overall financial performance of the variable does not affect the amount of lending. Conclusions and Suggestions for the company. Financial performance PT. BPR Setia Karib Abadi in healthy condition in rate of the years and have strange influence to total loans.Company mus be order to always strive to maintain the condition of its financial performance and careful - cautious in lending to bank soundness is maintained with a healthy category. Because PPAP and LDR influence on lending.